Implementation of Economic Crime After The Provision of Law Number 11 of 2021 Concerning The Prosecutor - Supardi . (Faculty of Law, Universitas Pekalongan, 2022)
The Criminalization of Economic Crimes occurred on May 11, 1995 which was marked by the birth of the Law on Economic Crimes (UUTPE). Since the birth of the law, the term